Differential methylation of enhancer at IGF2 is associated with abnormal dopamine synthesis in major psychosis - Pai, Shraddha; Li, Peipei; Killinger, Bryan; Marshall, Lee; Jia, Peixin; Liao, Ji; Petronis, Arturas; Szabó, Piroska E.; Labrie, Viviane (Nature communications, 2019)
Impaired neuronal processes, including dopamine imbalance, are central to the pathogenesis of major psychosis, but the molecular origins are unclear. Here we perform a multi-omics study of neurons isolated from the prefrontal cortex in schizophrenia and bipolar disorder (n = 55 cases and 27 controls). DNA methylation, transcriptomic, and genetic-epigenetic interactions in major psychosis converged on pathways of neurodevelopment, synaptic activity, and immune functions. We observe prominent hypomethylation of an enhancer within the insulin-like growth factor 2 ( IGF2 ) gene in major psychosis neurons. Chromatin conformation analysis revealed that this enhancer targets the nearby tyrosine hydroxylase ( TH ) gene responsible for dopamine synthesis. In patients, we find hypomethylation of the IGF2 enhancer is associated with increased TH protein levels. In mice, Igf2 enhancer deletion disrupts the levels of TH protein and striatal dopamine, and induces transcriptional and proteomic abnormalities affecting neuronal structure and signaling. Our data suggests that epigenetic activation of the enhancer at IGF2 may enhance dopamine synthesis associated with major psychosis. Dopamine dysregulation is centrally linked to major psychosis. Here, the authors characterise the hypomethylation of an enhancer within the insulin-like growth factor 2 gene in neurons of patients with major psychosis and provide evidence that this enhancer targets the tyrosine hydroxylase gene, responsible for dopamine synthesis.